Isolation and identification of Astragalin and 2-methoxy tyrosol from the bulbs of Allium paradoxum - Fatemeh Ghavam-Haghi; Masoud Sadeghi Dinani (Shahrekord University of Medical Sciences, 2017)
Introduction: Allium paradoxum is a perennial herb in northern Iran, especially in Mazandaran province. It is locally called "Alezi" and in addition to using as raw vegetable, is also used in the preparation of regional foods. This study was aimed to investigate the main phenolic constituents of the plant. Methods: Bulbs of the plant were extracted respectively by hexane, chloroform, chloroform-methanol (9-1) and methanol in a stepwise method with increasing solvent polarity. Methanol extract was then partitioned between water and butanol. Chloroform-methanol and butanol extract constituents were isolated and purified by column chromatography and HPLC. Chemical structure of the compounds was elucidated unambiguously by spectroscopic methods, including 1D and 2D NMR and MS spectroscopy. Results: Phytochemical investigation of A. paradoxum led to the isolation of two main phenolic compounds, a flavonoid glycoside and a tyrosol derivative. The isolated compounds were identified as kaempeferol-3-O-glucoside (1) (Astragalin) and 2-methoxy-2-(4'-hydroxyphenyl) ethanol (2-Methoxy tyrosol) (2). Conclusion: Isolation and identification of astragalin and 2-methoxy tyrosol from A. paradoxum is reported for the first time in this study and provide a chemical basis for the explanation of pharmacological and biological activities attributed to the plant.